PENGARUH STRATEGI PROMOSI MEDIA SOSIAL INSTAGRAM, CITRA MEREK, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK HITO COFFEE BEKASI - Humam Hanif Nasution; Nobelson Syarief; Yudi Nur Supriadi (Gapenas Publisher, 2022)
This study aims to determine and analyze the effect of Instagram's social media promotion strategy, brand image, lifestyle on purchasing decisions for Hito Coffee Bekasi products. This research method uses quantitative methods with 75 consumers of Hito Coffee respondents in Bekasi with purposive sampling technique. The data analysis technique was taken through a questionnaire with descriptive data analysis techniques then tested for validity and reliability then continued with hypothesis testing using SmartPLS 3.0. Hypothesis testing in this study used the analysis of the inner model, outer model, and t-statistical test with a significance level of 5% (0.05). The results showed that (1) the Instagram social media promotion strategy variable had a positive and significant effect on purchasing decisions (2) the brand image variable had a positive and significant effect on purchasing decisions (3) the lifestyle variable had no significant effect on purchasing decisions